Managing acutely aggressive or agitated people in a psychiatric setting: a survey in Lebanon - Dib, Joseph E.; Adams, Clive E.; Kazour, Francois; Tahan, Fouad; Haddad, Georges; Haddad, Chadia; Hallit, Souheil (Tehran University of Medical Sciences, 2018)
Background: Violent patients constitute 10% of all psychiatric admissions. Treatment options and clinical practice interventions vary across the globe and no survey of practice in a Middle Eastern setting exists. Surveying treatments in Lebanon will show treatment interventions used in this part of the world and, most importantly, provide the treatment options that could potentially be used for clinical trials pertaining to emergency psychiatry. Methods: A survey of clinicians’ opinions and practice was conducted between July and August 2017 at the largest psychiatric hospital in Lebanon. Results: Five of seven experienced psychiatrists provided opinions when interviewed of their preferred intervention when dealing with an emergency psychiatric episode. Whilst this varied in detail, there was a consistent view that there should first be verbal control, then use of medications, and finally physical restrain of the patient. A total of 39 emergency episodes (28 people) occurred in the one month (64% men in their 30s). Bipolar disorder was the most frequent single diagnosis behind the aggression (n=16, 41%; 12 people 43%) but the combined schizophrenia-like illnesses underlay 18 of the 39 episodes (46%; 13/28 people 46%). In clinical life, we found evidence of high family involvement, but little attempts made at initial verbal control in the hospital. All 39 episodes involved administration of pharmacological interventions. Medications were used in 29 of cases (74%) and non-medication interventions used in the remaining 10/39 (26%). Conclusion: This survey provides some evidence that clinicians’ preferences may not fully reflect clinical practice but also that experienced clinicians are using several clearly effective techniques to manage these very difficult situations. However, as for other parts of the world, treatment in Lebanon has limited or no underpinning by evidence from well-designed, conducted and reported evaluative studies.